Overexpression of NLRP3, NLRC4 and AIM2 inflammasomes and their priming‐associated molecules (TLR2, TLR4, Dectin‐1, Dectin‐2 and NFκB) in Malassezia folliculitis. Issue 2 (13th October 2017) - Liang, Ni; Yang, Yan‐Ping; Li, Wei; Wu, Ya‐Yun; Zhang, Zi‐Wei; Luo, Yun; Fan, Yi‐Ming
Summary: The activation of NLRP3, NLRC4 and AIM2 inflammasomes is pivotal for innate immunity against some pathogenic fungi, but their role in the pathogenesis of Malassezia folliculitis (MF) remains unclear. The objective of the study was to determine the expression of 4 canonical inflammasomes (NLRP1, NLRP3, NLRC4 and AIM2) and their priming‐associated molecules (TLR2, TLR4, Dectin‐1, Dectin‐2 and NFκB) in MF lesion. Expression of NLRP1, NLRP3, NLRC4, AIM2, caspase‐1, IL‐1β, TLR2, TLR4, Dectin‐1, Dectin‐2 and NFκB was detected by immunohistochemistry in skin lesion of 23 MF patients and normal skin of 12 healthy subjects. Furthermore, NLRP1, NLRP3, NLRC4, AIM2, caspase‐1 and IL‐1β mRNA was measured by quantitative real‐time PCR (qRT‐PCR) in 12 MF cases and 10 controls. Immunohistochemical analysis revealed that NLRP3, NLRC4, AIM2, Casp‐1, IL‐1β, TLR2, TLR4, Dectin‐1, Dectin‐2 and NFκB expression was up‐regulated in the epidermis and dermal inflammatory cells of MF lesion compared with control skin ( P < .01‐.05), but NLRP1 expression was not different between both groups ( P > .05). qRT‐PCR showed that levels of NLRP3, Casp‐1 and IL‐1β mRNA were significantly increased ( P < .01‐.05), whereas those of NLRP1, NLRC4 and AIM2 mRNA were slightly augmented compared to control skin ( P > .05). Our observation suggests that simultaneous activation of NLRP3, NLRC4 and AIM2 inflammasomes may play an important role in the pathogenesis of MF.